It is -8 and 7.
-8 x 7 = -56.
-8 + 7 = -1
Hope This Helps You!
Good Luck Studying :)
Answer:
<em>4 + 7x – 2</em>
Step-by-step explanation:
<u>Equivalent Expressions</u>
Let's find out which expressions are equivalent by simplifying them. One of the expressions should be not equivalent to the other three.
Simplifying
![2x + 2+ 2x + 3x -8=7x-6](https://tex.z-dn.net/?f=2x%20%2B%202%2B%202x%20%2B%203x%20-8%3D7x-6)
Now for the second expression
![4 + 7x -2=7x+2](https://tex.z-dn.net/?f=4%20%2B%207x%20-2%3D7x%2B2)
The third expression simplifies to
![-2 + 5x + 2x - 4=7x-6](https://tex.z-dn.net/?f=-2%20%2B%205x%20%2B%202x%20-%204%3D7x-6)
Finally, this is the simplification for the expression
![8x - x - 6=7x-6](https://tex.z-dn.net/?f=8x%20-%20x%20-%206%3D7x-6)
As seen, the only expression not equivalent to the other three is 4 + 7x – 2
Answer:
8.
Denote the equation : y = ax + b
Use the first 2 values of x and y in table:
3a + b = 21
5a + b = 35
Subtract the 2 equations:
=> 2a = 14 => a = 7 => b = 21 - 3 x 7 = 0
=> The solution is y = 7x
9.
Denote the equation : y = ax + b
Use the first 2 values of x and y in table:
5a + b = 17
10a + b = 22
Subtract the 2 equations:
=> 5a = 5 => a = 1 => b = 17 - 5 x 1 = 17 - 5 = 12
=> The solution is y = x + 12
Hope this helps!
:)
Option C is the right way to solve the equation.
Answer:
No they are proprotional.
Step-by-step explanation:
the tables eqaution is
y=3x+1